Mangrove Biodiversity Diversity E-Module-Based Teaching Material on Biodiversity Materials and Its Conservation Efforts at SMAN 3 Sungai Apit - Purwanto, Hadi; Irma, Wirdati; Apriani, Ade; Vilmala, Berry Kurnia; Shariq, Qadir Nawaz (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
The purpose of the study was to develop teaching materials based on e-modules. In addition, this study also aims to evaluate students' responses to e-module products created by using the ADDIE (Analysis, Design, Development, Implementation dan Evaluation). model for their development. The sample was selected using a purvosive sampling technique on 31 students from the science department at SMAN 3 Sungai Apit. Data were collected through observation, interviews, FGDs, validation sheets and questionnaires. Following the collection of all the data, the researcher performed identification by comparing the data with many mangrove guidebooks, including the mangrove guide book.Following the collection of all the data, the researcher identified the data by cross-referencing it with many mangrove guidebooks, including the mangrove guidebook. Results show that the e-module product is very feasible to use,With the level of approval from material experts of 96.75% (very feasible), learning experts of 87.5% (very feasible), media experts of 92.77% (very feasible) ), and teachers as users of 95.14% (very feasible). From the results of the questionnaire distributed to students, a positive response of 94.51% (very good) was obtained. Students also stated that the product was very easy to use, could increase learning motivation, and could increase students' knowledge about the diversity of mangroves in Sungai Apit. Therefore, it can be concluded that the product is very feasible and received positive responses from all parties, so that it can be distributed more widely. Keywords: development of teaching materials, mangroves, e-modules